1981
DOI: 10.1113/jphysiol.1981.sp013916
|View full text |Cite
|
Sign up to set email alerts
|

The nature of afferents from the large dorsal neck muscles that project to the superior colliculus in the cat.

Abstract: 1. A 3.5‐5 mm passive stretch of dorsal neck muscles at velocities of 50 mm/sec, a stimulus adequate to excite most neck muscle spindles, was usually ineffective in eliciting unit discharge in the superior colliculus. The sudden release of muscle tension was effective and excited fifty‐seven of sixty‐seven units tested. 2. When electrical stimulation of neck muscle nerves was used, a stimulus strength sufficient to excite Group III muscle afferents was usually required to elicit unit discharge in the superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Assuming that proprioceptors within the soft tissues of the neck are the primary source of head-on-body information, what then are the possible routes by which this information accesses the SC? Subcortical routes are certainly plausible, given the effects of neck muscle stimulation on SC activity in anesthetized cats (Abrahams and Rose 1975;Abrahams and Turner 1981) and the termination of neck muscle afferents in brain stem areas, which themselves project to the primate SC (Edney and Porter 1986). However, neck proprioceptive information is commonly combined with vestibular information at many subcortical centers, including the vestibular nuclei and cerebellum (for review, see Richmond and Corneil 2001), yet the apparent selective sensitivity of SC neurons to proprioceptive stimulation requires segregation of proprioceptive and vestibular information.…”
Section: Possible Sources and Routes Of Head-position Input To The Sumentioning
confidence: 99%
“…Assuming that proprioceptors within the soft tissues of the neck are the primary source of head-on-body information, what then are the possible routes by which this information accesses the SC? Subcortical routes are certainly plausible, given the effects of neck muscle stimulation on SC activity in anesthetized cats (Abrahams and Rose 1975;Abrahams and Turner 1981) and the termination of neck muscle afferents in brain stem areas, which themselves project to the primate SC (Edney and Porter 1986). However, neck proprioceptive information is commonly combined with vestibular information at many subcortical centers, including the vestibular nuclei and cerebellum (for review, see Richmond and Corneil 2001), yet the apparent selective sensitivity of SC neurons to proprioceptive stimulation requires segregation of proprioceptive and vestibular information.…”
Section: Possible Sources and Routes Of Head-position Input To The Sumentioning
confidence: 99%
“…However, muscle spindles can only account for a minority of the small myelinated fibres and the peripheral origin of the remainder has never been determined. The nature of the sensory receptors supplied by these axons became of particular interest when electrophysiological experiments showed that projections from cervical dorsal rami * Present address: Department of Physiology, University College, Gower Street, London WClE 6BT,UK. V. C. ABRAHAMS, B. LYNN AND F. J. R. RICHMOND to the superior colliculus and the spinal nucleus of the Vth cranial nerve (Abrahams & Yokota, 1979;Abrahams & Turner, 1981) originated from myelinated afferents with a high threshold for electrical excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of a number of stimuli, including natural stimuli to activate output neurones of the superior colliculus has also been investigated and the nature of input from neck muscle receptors has also been re-examined. These latter studies were prompted by recent findings (Abrahams & Turner, 1981;Abrahams, Lynn & Richmond, 1984) which suggested that the extensive nuchal input to the superior colliculus arises not from neck muscle as originally supposed (Abrahams & Rose, 1975 a), but from cutaneous receptors. Some preliminary accounts of this work have appeared Abrahams, Clinton & Downey, 1986).…”
Section: Introductionmentioning
confidence: 99%